TO EVALUATE THE COMPARATIVE STUDY OF “ONLAY” VERSES “SUBLAY” MESHPLASTY IN VENTRAL HERNIAS - Bushra Jameel; Rehman Ghulzar; Abid Rashid et al. (Journal of University Medical & Dental College, 2014)
ABSTRACT: INTRODUCTION: Ventra hernia refer to fascial defect of the anterolateral abdominal wall through which intermittent or continuous protrusion of abdominal tissue or organ may occurs. Effective repair of ventral hernia must include a tension free approach using mesh. The treatment of ventral hernia have changed radically over the last decade, however controversy still exist concerning mesh type, mesh positioning, operation method. The prosthetic mesh can be positioned by onlay, inlay and sublay technique. As onlay, inlay mesh repair are associated with lot of post operative complications the sublay mesh repair has been proposed as the gold standard by many surgeon OBJECTIVE: The aim of this study was to compare the sublay mesh repair with onlay mesh repair in patients with ventral hernia in term of post operative complications. STUDY DESIGN: Surgical unit-III, Allied Hospital, Punjab Medical College, Faisalabad. DURATION OF STUDY: 1 year after approval of synopsis. SAMPLE SIZE: Total of 334 patient, which were divided in two equal groups of 167 each; group A (167 patients) underwent onlay mesh repair and group B (167 patients) underwent sublay mesh repair. SAMPLING TECHNIQUE: Non probability consecutive sampling. RESULTS: Both techniques of operation were compared term of post operative complications, duration of operation and post operative hospital stay. Appropriate statistical test (chi square test) was applied. P value < 0.05 was taken significant. Data was analyzed by SPSS version 10. Our study showed that sublay mesh repair was associated with comparatively less frequency of post operative complications ( seroma 7.8%. vs 18.6%, hematoma 6.6% vs 15.6%, wound infection 10.8% vs 22.8% and sinus formation 4.8% vs 12.0% ) and these differences were significant statistically. CONCLUSION: For treatment of ventral hernia sublay mesh repair is associated with less post operative complications then the onlay mesh repair